UNLIKELY BEDFELLOWS: THE EVOLUTION OF THE RELATIONSHIP BETWEEN ENVIRONMENTAL PROTECTION AND DEVELOPMENT. Issue 1 (21st December 2016) - Brighton, Claire
Abstract: Poverty and environmental degradation are two of the gravest issues facing the planet today. The most obvious means of addressing each issue, however, appears ostensibly to undermine the other. While environmental and development strategies are largely associated with the concept of sustainable development that emerged in the 1990s, the debate between these two interests dates back to the 1940s. This article seeks to fill an apparent gap in environmental scholarship by presenting a history of the environmental protection/development relationship. It will argue that, rather than being the product of an organic development process, the concept of sustainable development and the principles underlying it were consciously shaped by a number of international actors with vested interests in their trajectory. Understanding why and how this was permitted is important not only for its capacity to throw light on the past, but also for its ability to assist in understanding and predicting the future.